“Ansiedad y consumo de tabaco en los estudiantes de la Carrera de Psicología Clínica, de la universidad nacional de Chimborazo, periodo abril-septiembre 2016”. - Damián Carrión., Paulo César (2017)
The present research entitled "Anxiety and tobacco consumption in students of the Clinical Psychology Major of the National University of Chimborazo, period April to September 2016" aims to: determine the influence of anxiety on tobacco consumption in the students of the Clinical Psychology Major. The studied population was 277 students and the sample was selected under inclusion and exclusion criteria, which constitute 65 students who meet the Hamilton Anxiety Scale and Fagestrom Test. The research design was non experimental quantitative, the type of research is field and cross-sectional and the level of research is descriptive. Data collection techniques and instruments are: Hamilton´s Anxiety Scale (HARS) and the Nicotine Dependence Fagestrom test (FTND). The techniques for the analysis of the results are processed using the basic statistics in excel program and the results are presented though tables and graphs for late clonclusions and recommendations. At the end of the research, the results show that students with Anxiety and Tobacco Consumption are 65 which represents 23% wich means that there is no significant relationship between anxiety and Tobacco Consumption. For that, psychoeducational workshops reduce anxiety and prevent dependence on tobacco, aimed at students of the Clinical Psichology Major of the National University of Chimborazo, were proposed.